Star Fruit Water Stew (Averrhoa Blimbi L.) as Antitussive and Expectorant in Acute Respiratory Infections - Nurlela, Lela; Harfika, Meiana (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2019)
Acute respiratory tract infections are acute respiratory tract infections that attack the throat, nose and lungs that last for approximately 14 days, acute respiratory infections regarding the structure of the duct above the larynx, but most of these diseases affect the upper and lower tract parts in a stimulanting or sequential manner . The purpose of this study was to analyze star fruit stew as an antitussive and expectorant in acute respiratory infections.The method used is an experimental approach. The population of this study was 40 respondents, acute respiratory infection sufferers of all ages in the village of Sedati, Sidoarjo Regency. Data collection techniques with non-probability sampling by purposive sampling as many as 20 respondents. The instrument used was an observation sheet.Based on the fisher exact test results, the results in the treatment group p value are 0.0001 which means that there is an effect of starfruit stew water on acute respiratory infections. In the control group the results obtained p value 0.083, which means that there is no effect on the control group. There is a difference between the treatment group and the control group.Star fruit more specifically can be a powerful drug to relieve coughing that occurs in acute respiratory infections, therefore it is important for local residents to consume starfruit stew water.